1998
DOI: 10.1002/(sici)1099-1565(199807/08)9:4<162::aid-pca394>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

An assay for secologanin in plant tissues based on enzymatic conversion into strictosidine

Abstract: The secoiridoid glucoside secologanin is the terpenoid building block in the biosynthesis of terpenoid indole alkaloids. A method for its determination in plant tissues and in cell suspension cultures has been developed. This assay is based on the condensation of secologanin with tryptamine, yielding strictosidine, in a reaction catalysed by the enzyme strictosidine synthase (STR; E.C. 4.3.3.2). Subsequently, the formation of strictosidine is quantified by high performance liquid chromatography (HPLC). STR was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…This result was unexpected as it has been postulated that secologanin is accumulated in young leaves to provide protection against pathogen attack. Indeed, Hallard et al (1998) reported relatively high levels of secologanin in leaves of L. xylosteum whereas in the present study the highest levels of secologanin were detected in stems of L. tatarica plants (Fig. 3b).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This result was unexpected as it has been postulated that secologanin is accumulated in young leaves to provide protection against pathogen attack. Indeed, Hallard et al (1998) reported relatively high levels of secologanin in leaves of L. xylosteum whereas in the present study the highest levels of secologanin were detected in stems of L. tatarica plants (Fig. 3b).…”
Section: Discussionmentioning
confidence: 99%
“…3b). However, loganin, as well as secologanin, can act as a feeding deterrent against herbivores (Hallard et al 1998;Rimpler 1991).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations